ANALISIS DETERMINAN LAMA RAWAT INAP PASIEN STROKE DI RUMAH SAKIT UMUM DAERAH KLUNGKUNG MENGGUNAKAN ANALISIS KESINTASAN - Darmapadmi, Luh Putu Kartika; Widarsa, I Ketut Tangking; Mulyawan, Ketut Hari (ARCHIVE OF COMMUNITY HEALTH; Vol 5 No 1 (2018): Juni (2018), 2020)
ABSTRACT The length of stay is a major factor affecting the cost burden of inpatient stroke patients. This study aims to identify the determinant of length of stay stroke patient hospitalized at RSUD Klungkung in 2016. This study used a retrospective cohort design. The total sampling method used in sample selection and selected 149 stroke patients hospitalized at RSUD Klungkung in 2016. Secondary data was collected by reviewing medical record of sample file. Analysis was performed using survival analysis by Kaplan-Meier method and Cox Regression. Results showed that the median length of stay among stroke patients was 9 days. The median length of stay among stroke patients with diabetes mellitus, medical complications during hospitalization and hemorrhagic stroke was 7 (CI 95%: 6 - 8) days, 11 (CI 95%: 7 - -) days and 15 (CI 95%: 14 - 17) days. Diabetes mellitus, medical complications and types of stroke are factors that affect the length of stay among stroke patients with HR = 1.82 (CI 95%: 1.09 - 3.06), HR = 2.73 (CI 95%: 1.36 - 5.46) and HR = 3.52 (CI 95%: 1.89 - 6.57). Based on the type of stroke, diabetes mellitus had significant effect on the length of stay among ischemic and hemorrhagic stroke patient with HR = 1.74 (CI 95%: 1.01 - 2.99) and HR = 2.26 (CI 95%: 5.78 - 8.87). Meanwhile, medical complication had significant effect among ischemic stroke patient only with HR = 2.65 (CI 95%: 1.24 - 5.68). Major determinan affecting length of stay among stroke patient at RSUD Klungkung was diabetes mellitus, medical complication and type of stroke. It is advisable to control the risk factors through integration with Prolanis programs and improve the management especially in hemorrhagic stroke patient to shorten the length of stay and decreased mortality rate. Keywords : Determinant, Length Of Stay, Stroke, RSUD Klungkung